Pengaruh Kadar Karbondioksida (CO2) dan Nitrogen (N2) Pada Karakteristik Pembakaran Gas Metana - Wahyudi, Djoko; Wardana, ING; Hamidi, Nurkholis (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
One of the renewable energy is biogas. Biogas has a great chance in its development. Biogas resulted from fermentation process is consists of: CH4 (55-75%), CO2 (25-45%), H2 (1- 5%), N2 (0-0.3%), O2 (0.1-0.5%), and H2S (0-3%). If biogas is cleared from polluter well it will have the same characteristics with natural gas. Components of the polluter water (H2O), hydrogen and as sulfide (H2S), carbon dioxide (CO2) and some particulates should be eliminated to achieve pipeline quality gas. In order to understand how the influence of the levels of CO2 and N2 of the methane combustion characteristic. The observation was conducted experimentally by burning a mixture of stoichiometry (methane gas and air) with a percentage of CO2 and N2 in the transparent fuel square-shaped space with dimensions 500 x 200 x 10 mm. The results showed that the levels of CO2 and N2 affect the combustion process, it causing the blue flame to be fade.It indicated the combustion is not perfect and the levels of CO2 and N2 inhibits the collision reaction between molecules of methane gas and air molecules. The result also showed that CO2 reduce the flame speed. Keywords: energy, CO2, N2, combustion characteristic, methane gas, air